Ethanol Extract Cream of Jackfruit Tree Bark (Arthocarpus Heterophilus) is Equally Effective with Hydroquinone Cream on Preventing the Increase of Melanin on Guinea Pigs Skin (Cavia porcelus) Exposed to Ultraviolet B Ray - Indiradewi Hastiningsih (Journal of Global Pharma Technology, 2016)
Introduction: Ethanol extract of jackfruit tree bark (Artocarpus heterophillus) contains antioxidants, phenolic substances, tannin, steroid, linoleic acid ethyl ester, and vitamin C which can inhibit the elevation of melanin levels on epidermal tissue. Hydroquinone (HQ) was used as comparison because HQ is the gold standard of hyperpigmentation therapy. Method: This research is a laboratory experimental research using randomized post-test only control group design with 30 male guinea pigs (Cavia Porcelus) divided into 3 groups with 10 individuals on each group, with control group given base cream, group 1 was administered 4% hydroquinone cream, and group 2 was administered 4% jackfruit tree bark extract cream. All intervention groups were exposed with UV-B ray with total dose of 390 mJ/cm² three times in a week for 2 weeks, and underwent biopsy of their skin sample to examine the amount of melanin on the epidermal layer. Result: The result of our research showed the mean amount of melanin on control group was 54.33±4. 51%, group 1 was 3.01± 0.89% and group 2 was 4.23± 1.82%. There is a significant difference between control group and both group 1 and 2 in inhibiting the increase of melanin amount on epidermal tissue (p<0.05). There is no significant difference between group 1 and 2 on inhibiting the increase of melanin amount on epidermal tissue (p>0.05). Conclusion: We conclude that 4% jackfruit tree bark extract cream can prevent the increase of melanin amount on guinea pigs’ skin epidermal layer. The 4% jackfruit tree bark extract cream is equally effective to 4% hydroquinone cream on preventing the elevation of melanin amount on epidermal layer of guinea pig’s skin exposed with UV-B ray.Keywords: Jackfruit tree bark extract cream, Melanin amount, UV-B ray.